2009
DOI: 10.1097/fbp.0b013e32832a8f66
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the behavioral mechanisms of antipsychotic action using a drug–drug conditioning paradigm

Abstract: Antipsychotic drugs at noncataleptic doses selectively suppress conditioned avoidance response in rats. In our previous study, we had used a two-way active avoidance response paradigm to show that the antipsychotic-induced interoceptive state is one of the mechanisms underlying the avoidance-disruptive effect of antipsychotics. In this study, we sought to further examine this mechanism using a novel drug–drug conditioning procedure. We made use of the fact that both the typical neuroleptic haloperidol and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…The answer to both questions is yes. We demonstrated that OLZ sensitization and CLZ tolerance could be induced in adolescent rats using the same procedure (ie, an induction phase followed by a challenge test) as employed in adult rats (Li et al, 2004;Li et al, 2007;Li et al, 2009a;Li et al, 2009b;Li et al, 2010;Mead and Li, 2010;Li et al, 2012;Zhang and Li, 2012). They mainly manifested in the avoidance response (a behavioral measure of antipsychotic activity) and/or intertrial crossing (a behavioral measure of motor function/sedation), but not in the 22 kHz USV (an index of anxiolytic property), suggesting that they are behaviorally specific (Stewart and Badiani, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The answer to both questions is yes. We demonstrated that OLZ sensitization and CLZ tolerance could be induced in adolescent rats using the same procedure (ie, an induction phase followed by a challenge test) as employed in adult rats (Li et al, 2004;Li et al, 2007;Li et al, 2009a;Li et al, 2009b;Li et al, 2010;Mead and Li, 2010;Li et al, 2012;Zhang and Li, 2012). They mainly manifested in the avoidance response (a behavioral measure of antipsychotic activity) and/or intertrial crossing (a behavioral measure of motor function/sedation), but not in the 22 kHz USV (an index of anxiolytic property), suggesting that they are behaviorally specific (Stewart and Badiani, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Using such a paradigm, we show that repeated treatment of haloperidol and olanzapine (OLZ) induce a sensitization effect in both the induction and expression phases (Li et al, 2009b;Li et al, 2009a;Sun et al, 2009;Li et al, 2010;Mead and Li, 2010;Zhao et al, 2012). In contrast, repeated treatment of clozapine (CLZ) does not cause an apparent sensitization or tolerance during the induction phase (Sun et al, 2009;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Olanzapine (OLZ) 0.5, 1.0, and 2.0 mg/kg (subcutaneous [sc]; gifts from the NIMH drug supply program) were dissolved in distilled sterile water with 1.0–1.5% glacial acetic acid. The 1.0 and 2.0 mg/kg OLZ acutely inhibit CAR without inducing catalepsy based on our previous work (Feng et al , 2013; Li et al , 2004, 2007, 2009; Mead and Li, 2010; Qiao et al , 2013a, 2013b; Sun et al , 2009; Zhang and Li, 2012; Zhao and Li, 2010). The lower challenge dose of 0.5 mg/kg OLZ has been successfully used in our previous studies (Mead and Li, 2010; Qiao et al , 2013a; Sparkman and Li, 2012; Swalve and Li, 2012; Zhang and Li, 2012) and prevents the floor effect (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, we have used the conditioned avoidance response (CAR) model, a well-established animal model with high predictive validity for antipsychotic action (Wadenberg and Hicks, 1999), to investigate the long-term effects of repeated antipsychotic treatment (Li et al ., 2004b, 2007, 2009a, 2009b, 2010; Mead and Li, 2010). We showed that repeated treatment with haloperidol (HAL; a typical antipsychotic), olanzapine (OLZ), and risperidone (atypical antipsychotics) produces a progressively-enhanced disruption of avoidance responding over 7 days (Li et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%